Digital Literacy Education: The Role of Language in Resolving Communication Conflicts on Social Media - Muh. Hartawan; Nurhayati, St. (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study aims to investigate digital literacy education, which enhances users' technical skills and fosters ethical and effective communication competencies. This study emphasizes the use of language as a mechanism for resolving communication problems on social media. This research employs a qualitative methodology. This study aims to analyze public perceptions of political dynamics, polarization, and voter engagement, as well as the influence of social media on the dissemination of information and opinions concerning the election. Data is gathered via interviews and focus group sessions. We employed a descriptive qualitative data analysis methodology. The study's results suggest that the ramifications for digital literacy education are substantial in the context of the election. Education that fosters a critical comprehension of language in social media, the capacity to identify biased or misleading material, and the proficiency in ethical and effective communication can mitigate communication disputes and enhance the quality of political discourse. Another conclusion indicates that language significantly influences the quality of communication on social media, subsequently impacting the democratic process and voter engagement in elections. Moreover, social media can serve as a crucial medium to enhance voter engagement, provided that the language employed stimulates public interest and comprehension of the electoral process. This paper integrates the methodologies of the philosophy of language and digital communication studies, contributing to the discourse on fostering peaceful interactions in cyberspace and offering good implications for digital literacy education.